2021
DOI: 10.1111/1471-0307.12795
|View full text |Cite
|
Sign up to set email alerts
|

Whey protein hydrolysis with microbial proteases: Determination of kinetic parameters and bioactive properties for different reaction conditions

Abstract: Whey protein concentrate was enzymatically hydrolysed with the microbial proteases Alcalase ® and Flavourzyme ® under different experimental conditions. The effect of the reaction variables on the properties of the hydrolysates was evaluated. The pH had a significant effect both on the degree of hydrolysis and on the kinetic parameters. The initial substrate concentration and the enzyme/substrate (E/S) ratio had an influence both on the degree of hydrolysis and on the hydrophobicity index, but not on the bioac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
1
7
1
1
Order By: Relevance
“…Hydrolysis using Alcalase ® resulted in higher ORAC and TEAC values compared to WPC hydrolysis with Prolyve ® . These results concur with those reporting higher antioxidant activities in Alcalase ® -generated WPHs as opposed to other enzyme preparations [ 36 , 43 , 44 ]. On the other hand, hydrolysis of WPC80 using both Alcalase ® and Prolyve ® in this study did not show an improvement in FRAP value (9.21–15.97 µmol TE/g) compared to WPC80 (15.03 ± 1.78 µmol TE/g) ( Figure 5 c).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Hydrolysis using Alcalase ® resulted in higher ORAC and TEAC values compared to WPC hydrolysis with Prolyve ® . These results concur with those reporting higher antioxidant activities in Alcalase ® -generated WPHs as opposed to other enzyme preparations [ 36 , 43 , 44 ]. On the other hand, hydrolysis of WPC80 using both Alcalase ® and Prolyve ® in this study did not show an improvement in FRAP value (9.21–15.97 µmol TE/g) compared to WPC80 (15.03 ± 1.78 µmol TE/g) ( Figure 5 c).…”
Section: Resultssupporting
confidence: 92%
“…Similar DH values in the WPHs generated under FF and ST conditions was previously reported during Alcalase ® hydrolysis of whey protein isolate (WPI) [ 17 ] and during WPC80 hydrolysis using papain [ 16 ], FlavourPro ® Whey and Debitrase ® HYW20 [ 15 ]. Eberhardt et al [ 36 ] reported that pH significantly influenced the DH value of WPC80 hydrolysed with Alcalase ® . The highest DH value (23.1%) was achieved when hydrolysis was carried out using ST conditions at pH 9.0, an E:S of 2% ( w / w ) and 10% ( w / v ) WPC80, while ST at pH 7.0 yielded the lowest DH value (16.9%).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, for a better interpretation of the results, a hydrophobicity index (HI%) was calculated following Eberhardt et al . (2021). As shown in Table S3 (Supporting Information), both low and medium hydrophobicity index resulted in nonsignificant differences, independently of the sample pools and the assayed DH.…”
Section: Resultsmentioning
confidence: 99%
“…The most valuable component of whey is protein, which is a source of essential amino acids and bioactive peptides possessing antioxidant, antihypertensive, antithrombotic, immunomodulatory, and antimicrobial activity. Enzymatic hydrolysis of whey proteins allows to increase their biological value, decrease allergenicity, improve functional properties, making it possible to use the resulting hydrolysates in functional food production [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of enzyme preparations (EPs) of animal, plant and microbial origin are used for the whey proteins hydrolysis. Studies have shown the potential for the use of bacterial serine proteases (EC 3.4.21.62) -EP Alcalase (Novozymes A/S) and a complex preparation of fungal exo-and endopeptidases with high leucine aminopeptidase activity -Flavourzyme (Novozymes A/S) in whey protein hydrolysis [7,10]. The best results were obtained when using a two-stage sequential treatment of milk protein concentrate with Alcalase and Flavourzyme [11].…”
Section: Introductionmentioning
confidence: 99%